Presentism and actualism - Noonan, Harold (Springer, 2018)
Presentism, some say, is either the analytic triviality that the only things that exist now are ones that exist now or the obviously false claim that the only things that have ever existed or will are ones that exist now. I argue that the correct understanding of presentism is the latter and so understood the claim is not obviously false. To appreciate this one has to see presentism as strictly analogous to anti-Lewisean actualism. What this modal analogue makes evident is that singular tensed statements can have scope ambiguities and so can be thought of as true with the temporal operator represented by the tense read as having wide scope. Secondly, I argue that the analogy with the modal case also makes it clear that presentism must be understood as a thesis of the form: ‘the only things that have ever existed or ever will exist stand in relation R to this (present) utterance’, and is not a substantive topic for debate until relation R is characterized in non-temporal terms. However, despite the strict analogy, I argue that presentism may be a harder position to defend than actualism, since the truth-maker objection, properly interpreted, with Lewis, as based on a supervenience thesis, has more force as an objection to presentism since supervenience is itself a modal notion.